2022
DOI: 10.1093/ibd/izac252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2 vs 3 Doses of COVID-19 Vaccine in Patients With Inflammatory Bowel Disease: A Population-based Propensity Matched Analysis

Abstract: Aim There are limited data on the impact of 2 vs 3 doses of COVID-19 vaccine in patients with inflammatory bowel disease (IBD). The primary aim of the study was to assess the efficacy of COVID-19 vaccine based on number of administered doses in patients with IBD. Methods We conducted a retrospective cohort study using TriNetX, a multi-institutional database to compare patients with IBD who received 1, 2, or 3 doses of BNT162b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Data privacy, security, attestation, and steps taken to ensure de-identification have been previously described. 12,13…”
Section: Methodsmentioning
confidence: 99%
“…Data privacy, security, attestation, and steps taken to ensure de-identification have been previously described. 12,13…”
Section: Methodsmentioning
confidence: 99%
“…However, vaccination was reported to be safe for both adults and children known to have IBD, with a low rate of vaccination-induced disease flare and a reduced risk of thrombotic events [23,[42][43][44]. Studies revealed that a third vaccine dose might be able to reduce COVID-19 incidence and lower the rates of severe outcomes, including hospital admission [45,46]. Schell and colleagues reported that IBD patients on biologics are susceptible to reinfection because of their weakened IgG response to natural SARS-CoV-2 infection [33].…”
Section: The Impact Of Covid-19 On the Incidence Outcomes And Managem...mentioning
confidence: 99%
“…Im klinischen Alltag ist insbesondere das aufklĂ€rende GesprĂ€ch bei großer Sorge der chronisch kranken Patienten vor der Infektion, aber auch vor Impfnebenwirkungen, wie sie u. a. fĂŒr Patienten mit chronisch-entzĂŒndlichen Darmerkrankungen publiziert sind, eine Herausforderung [ 29 ]. Ein vollstĂ€ndiger Impfschutz reduziert auch bei immunmodulierend behandelten Patienten mit chronisch-entzĂŒndlichen Darmerkrankungen das Risiko einer COVID-19-Ansteckung und das Risiko von schwerer COVID-19-VerlĂ€ufen [ 6 , 20 ]. Dabei wird in einer Metaanalyse aus 31 Studien mit 9447 Patienten eine Serokonversionsrate von 96 % nach vollstĂ€ndiger Impfung berichtet, wobei die Antikörpertiter bei Patienten unter alleiniger Tumornekrosefaktor(TNF)-α-Antikörper-Therapie oder in Kombination mit einem Immunmodulator rasch abfallen und im Verlauf kontrolliert werden sollten [ 19 ].…”
Section: Covid-19-impfung Und Autoimmunerkrankungenunclassified